2002
DOI: 10.1006/abio.2001.5503
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Decay Engineering

Abstract: Metallic surfaces can have unusual effects on fluorophores such as increasing or decreasing the rates of radiative decay and the rates of resonance energy transfer (RET). In the present article we describe the effects of metallic silver island films on the emission spectra, lifetimes, and energy transfer for several fluorophores. The fluorophores are not covalently coupled to the silver islands so that there are a range of fluorophore-to-metal distances. We show that proximity of fluorophores to the silver isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
537
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 608 publications
(574 citation statements)
references
References 54 publications
25
537
0
2
Order By: Relevance
“…In general, the quantum yield and lifetime of a fluorophore are described as 9,10 (9) (10) where Γ and k nr are the radiative and nonradiative decay rates, respectively. In proximity to the metallic surfaces and/or particles, eqs 9 and 10 are modified as (11) (12) The radiative decay rate is increased to N r Γ in the presence of plasmonic metal nanostructures. k nr ′ is the nonradiative decay rate in the presence of metal particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the quantum yield and lifetime of a fluorophore are described as 9,10 (9) (10) where Γ and k nr are the radiative and nonradiative decay rates, respectively. In proximity to the metallic surfaces and/or particles, eqs 9 and 10 are modified as (11) (12) The radiative decay rate is increased to N r Γ in the presence of plasmonic metal nanostructures. k nr ′ is the nonradiative decay rate in the presence of metal particles.…”
Section: Resultsmentioning
confidence: 99%
“…1 We have shown that the metal nanoparticles could change the radiative decay rates of fluorophores. [9][10][11][12] These changes occur because of modifications of the photonic mode density near the particle. Using metal nanoparticles, we could engineer changes in the emission based on the fluorophore-metal particle geometries.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that many factors can result in increased intensities from fluorophores. 42 The absolute and relative brightness of a fluorophore are dependent on the values of the radiative and nonradiative rates. Like a radiating antenna, a fluorophore acts as an oscillating dipole, and nearby metal surfaces can respond to the oscillating dipole and modify the rate of emission and the spatial distribution of the radiated energy.…”
Section: Resultsmentioning
confidence: 99%
“…We refer to this concept as the radiating plasmon model (RPM). 11,12 In addition, we have also recently reported the first observation of metal-enhanced chemiluminescence (MEC) where Silver Island films (a noncontinuous silver surface) in close proximity to chemiluminescing species significantly enhanced the luminescence intensity. 13,14 This suggested that surface plasmons can be directly excited by chemically induced electronically excited luminophores.…”
Section: Introductionmentioning
confidence: 99%